2020
DOI: 10.1002/anie.202004439
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Enabled Trifluoromethylative Pyridylation of Alkenes from Pyridines and Triflic Anhydride

Abstract: A general strategy for visible‐light‐enabled site‐selective trifluoromethylative pyridylation of unactivated alkenes has been developed using pyridines and triflic anhydride (Tf2O). Intriguingly, the N‐triflylpyridinium salts, generated in situ from pyridines and Tf2O, serve as effective modular bifunctional reagents to install both CF3 and pyridyl groups to various olefins while controlling C4‐selectivity in radical addition to the pyridine core. This synthetic route exhibited broad substrate scope under meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 95 publications
3
32
0
Order By: Relevance
“…On the basis of the above results and previous reports, , ,, a plausible mechanism for this reaction is proposed in Scheme . Initially, the reaction of Tf 2 O and 2,2′-bipyridine generates the corresponding N -triflylpyridinium salt A .…”
supporting
confidence: 65%
See 2 more Smart Citations
“…On the basis of the above results and previous reports, , ,, a plausible mechanism for this reaction is proposed in Scheme . Initially, the reaction of Tf 2 O and 2,2′-bipyridine generates the corresponding N -triflylpyridinium salt A .…”
supporting
confidence: 65%
“…In those reactions, the trifluoromethyl radical was formed by single electron transfer (SET) reduction of the in situ-generated N -triflylpyridinium salt with the excited-state photocatalyst . Very recently, Hong and co-workers described the introduction of both CF 3 and pyridyl groups into olefins using N -triflylpyridinium salts as modular bifunctional reagents under photocatalysis (Scheme c) . These works demonstrated that Tf 2 O is an attractive alternative trifluoromethyl radical reagent through a combination of pyridine activation and photoredox catalysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Qing and co-workers reported the first copper/zinc-copromoted chloro- and bromo-trifluoromethylation of alkenes and alkynes using inexpensive and simple materials such as trifluoromethanesulfonic anhydride (CF 3 SO 2 ) 2 O (Tf 2 O) [ 29 , 40 ] as trifluoromethylating reagent [ 41 ]. Thus, the reaction of alkenes and alkynes with Tf 2 O in the presence of copper salts such as CuX 2 (X = Br, Cl), Zn powder and 2,2′-bipyridine provided the corresponding bromo- or chlorotrifluoromethylated products in good yields.…”
Section: Chloro- and Bromotrifluoromethylationmentioning
confidence: 99%
“…Forschungsartikel products.T he structure of 3v was unambiguously confirmed by X-ray crystallographic analysis. [17] Notably,t he current method could be expanded to interesting examples of substrates containing privileged scaffolds,s uch as coumarin and flavone,a ffording the corresponding products 3z and 3aa.I ti sn oteworthy that this protocol can also be extended to the electron-rich alkene,N -vinyl phthalimide to yield the desired product 3ab.Inall cases,the reactions proceeded with C4-selectivity,and none of the C2-products were detected.…”
Section: Angewandte Chemiementioning
confidence: 99%